2019
DOI: 10.1534/genetics.119.301834
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation Through Lifestyle Switching Sculpts the Fitness Landscape of Evolving Populations: Implications for the Selection of Drug-Resistant Bacteria at Low Drug Pressures

Abstract: Novel genotypes evolve under selection through mutations in pre-existing genes. However, mutations have pleiotropic phenotypic effects that influence the fitness of emerging genotypes in complex ways. The evolution of antimicrobial resistance is mediated by selection of mutations in genes coding for antibiotic-target proteins. Drug-resistance is commonly associated with a fitness cost due to the impact of resistance-conferring mutations on protein function and/or stability. These costs are expected to prohibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 72 publications
1
26
0
Order By: Relevance
“…Mounting evidence now suggests that the evolutionary trajectories that sub-MIC selection can follow are different from those seen under conditions of high drug concentrations. In at least two different cases, sub-MIC drug pressures were also shown to select for very high-level drug resistance (2,3). The results obtained in the present study mirror these results conceptually, as Lon deficiency enhanced the level of trimethoprim resistance (i.e., the drug MIC) for several of the mutants tested.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Mounting evidence now suggests that the evolutionary trajectories that sub-MIC selection can follow are different from those seen under conditions of high drug concentrations. In at least two different cases, sub-MIC drug pressures were also shown to select for very high-level drug resistance (2,3). The results obtained in the present study mirror these results conceptually, as Lon deficiency enhanced the level of trimethoprim resistance (i.e., the drug MIC) for several of the mutants tested.…”
Section: Discussionsupporting
confidence: 83%
“…Further, the fitness advantage conferred by Lon deficiency at sub-MICs of trimethoprim is relevant in the context of selection under conditions of low drug pressure. Sub-MICs of antibiotics are likely to be encountered by bacteria in natural habitats such as soil and water and are known to select for clinically relevant drug resistance (2,3,43). Mounting evidence now suggests that the evolutionary trajectories that sub-MIC selection can follow are different from those seen under conditions of high drug concentrations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inhibitory Concentration-50 (IC50): IC50 of trimethoprim was determined using a broth dilution assay as described in Matange et al (2019) [40]and Matange et a. (2018) [33].…”
Section: Antibiotic Sensitivitymentioning
confidence: 99%
“…Previous work revealed that inactivation of the regulator fimE leads cells to shift their lifestyle from planktonic to pellicle-like growth in broth cultures without reducing the growth rate (Matange et al, 2019;Stentebjerg-Olesen et al, 2000). Pellicle formation by fimE inactivation was also observed to be selected for in E. coli cells exposed to the antibiotic rifamycin and was found to improve resistance by increasing cell aggregation due to increased cell adhesion (Matange et al, 2019). It is therefore possible that a similar mechanism also improves 5FU and FUDR resistance and can therefore explain the frequent inactivation of fimE in our evolution experiments.…”
Section: Evolved Mutations Influence Multiple Resistance Mechanismsmentioning
confidence: 99%